Infectious Salmon Anemia Virus-Genetics and Pathogenesis - Spencer-Ossa, E; Sandino-Garcia, A; Cortez-San Martin, M; Cottet-Bustamante, L (2011)
The infectious salmon anemia virus (ISAV) is the causative agent of the ISA syndrome that affects mainly Atlantic salmon (Salmo salar) and has caused high mortality epidemics in Norway, Scotland, Canada, the United States and Chile. It is classified as an Orthomyxoviridae, its genome is composed of 8 single-strand RNA segments with negative polarity that code for 11 polypeptides. Through functional studies of the coded proteins it has been established that RNA segments 5 and 6 code for a fusion protein and hemagglutinin, respectively, while two polypeptides coded by segments 7 and 8 inhibit interferon induction. The functions of the rest of the possible proteins coded by the viral genome have been assigned by comparison with the corresponding ones of the influenza virus genome. As to its pathogenicity, some growth parameters such as incubation period, resistance to chemical and physical factors, establishment of the infection in other marine species, and dissemination ability among the different organs have been evaluated in several salmonids. Genomic analysis has shown (i) the existence of a high polymorphism region (HPR) in segment 6, and (ii) sequence insertion in segment 5. More than 20 HPR variants have been determined, all originating from HPR0, which is associated with low pathogenicity, while 4 different sequence insertions in segment 5 have not been related with some characteristic of the virus infection. Much progress has been made in the characterization of the virus in 20 years of study, but more detailed knowledge of the specific function of the proteins coded by all the viral genes is still missing, including the pathogenicity mechanism at the molecular level. © 2010 Elsevier B.V.
Keywords: ISA virus